Strategies to Introducing Ecotourism Concept with Social Media for College Student in Malang - Pramana, Ida Idewa Agung Willy; Leksono, Amin Setyo; Djati, Moch. Sasmito (Graduate School, Universitas Brawijaya, 2019)
Indonesia categorized as a mega-biodiversity country, with 25% of the species in the world. One of the uses of natural resources is in the tourism sector. Lately, in Indonesia, research about Social Media and Ecotourism is still not much done. Some studies in Indonesia mostly still view social media as marketing advice. In fact, social media also plays an important role in regulating the perceptions of the people who come to the ecotourism site both from the content or the ease of access. Practically this research can be used as a strategic reference by stakeholders, to be able to use Social Media as media for promotion and education. Then academically, this research can be a reference for further research on the strategy of managing ecotourism with social media. This research is a descriptive type with quantitative and qualitative approaches, with research locations in Malang. Research using an online questionnaire with Google Form. The results are, Instagram is the most used social media by students in Malang. And for the management strategy with Instagram, it can be done with an aggressive strategy that is utilizing Strength and Opportunities from Instagram such as fast, cheap, environmentally friendly and widely used by students and can be more optimized with the AISAS strategy.Keywords: ecotourism, facebook, Instagram, Malang, social media, strategy, student.